2005
DOI: 10.4049/jimmunol.175.8.5288
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 Is Required for Induction but Not Maintenance of Protective, Memory Responses to Blastomyces dermatitidis: Implications for Vaccine Development in Immune-Deficient Hosts

Abstract: Cellular immunity mediated by T lymphocytes, in particular CD4+ and CD8+ type 1 (T1) cells, is the main defense against pathogenic fungi. IL-12 initiates T1 cell development and cell-mediated immunity, but it is unclear whether IL-12 contributes to the maintenance of an antifungal T1 response. In this study, we addressed the role of IL-12 for vaccine-induced memory T cell development against experimental pulmonary blastomycosis. CD4+ T cells absolutely required IL-12 to control a live genetically engineered at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…It is evident that most immunological adjuvants activate innate immune cells by pathogen-associated molecular patterns for TLRs leading to the generation of a costimulatory context capable of promoting T cell activation, proliferation, and differentiation that produces effector and memory T cells (7)(8)(9). However, recently chronic inflammation, typically characterized by abundant IL-12 production, has been shown to restrict CD8 T cell clonal expansion and memory generation (10).…”
Section: T He Cd8mentioning
confidence: 99%
“…It is evident that most immunological adjuvants activate innate immune cells by pathogen-associated molecular patterns for TLRs leading to the generation of a costimulatory context capable of promoting T cell activation, proliferation, and differentiation that produces effector and memory T cells (7)(8)(9). However, recently chronic inflammation, typically characterized by abundant IL-12 production, has been shown to restrict CD8 T cell clonal expansion and memory generation (10).…”
Section: T He Cd8mentioning
confidence: 99%
“…IL-12 is required for induction but not maintenance of memory T1 (type 1 T cell) responses [24]. Based on our data, we suspect that LV-SOCS1-siRNA-DCs produced more IL-12 in a feedback loop-enhanced manner to help induce the memory responses we saw.…”
Section: Discussionmentioning
confidence: 59%
“…Since IL-2, IL-7, IL-12, and IL-15 are important cytokines for memory T cell production and homeostasis [24,25], we hypothesized that downregulating the production of SOCS1 in dendritic cells might allow increased signaling to T cells by these and other cytokines, resulting in expanded memory Tcell populations. Enhanced antigen presentation by SOCS1-downregulated dendritic cells should also boost memory T cell production.…”
Section: Introductionmentioning
confidence: 99%
“…However, these factors, and even CD4 cells themselves (34), are dispensable in immunodeficient mice, illustrating the plasticity of vaccine immunity at both the cellular and the molecular levels (34,35). We have recently observed that interleukin-12 (IL-12) is required for the induction, but not maintenance, of protective memory responses against B. dermatitidis infection (36). Dispensability of IL-12 during the maintenance phase of antifungal memory immunity was unexpected and, to our knowledge, was not previously established during CMI to infectious diseases.…”
Section: Discussionmentioning
confidence: 99%